2008
DOI: 10.1124/dmd.108.023572
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Chemical and Antibody Inhibitors for Superior P450 3A Inhibition in Reaction Phenotyping Studies

Abstract: ABSTRACT:Cytochrome P450 (P450) reaction phenotyping is a key process toward accurately determining the contribution of different P450s to the metabolism of new chemical entities. The significance of P450s to drug disposition has led to the identification of selective chemical and antibody inhibitors for individual P450 enzymes. Despite these advances, the maximal inhibition attainable is limited by the use of inhibitor concentrations that maintain selectivity for the individual P450s. Thus, most commercially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…4, A-C). The formation of M2 (sulfoxidation) and M5 (21-hydroxylation) was inhibited with the CYP3A inhibitor ketoconazole (500 nM) plus a CYP3A-selective antibody, a combination known to produce a more complete and selective inhibition than either alone (Rock et al, 2008) (Fig. 4, E and F).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…4, A-C). The formation of M2 (sulfoxidation) and M5 (21-hydroxylation) was inhibited with the CYP3A inhibitor ketoconazole (500 nM) plus a CYP3A-selective antibody, a combination known to produce a more complete and selective inhibition than either alone (Rock et al, 2008) (Fig. 4, E and F).…”
Section: Resultsmentioning
confidence: 97%
“…The incubation was then diluted to 0.2 mg/ml microsomal protein in 100 mM potassium phosphate buffer (pH 7.4). Ketoconazole (500 nM) was added to the CYP3A4 incubation (Rock et al, 2008). Montelukast was added to the incubation mixture at a final concentration of 0.1 M. Control P450 substrate marker reactions, as reported previously (Walsky and Obach, 2004), were run to verify the effectiveness of the P450 antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, remaining activity can bring into question the P450 activity from less abundant hepatic P450s such as 2B6 and 2C8, which are showing increased metabolic activity toward numerous commercial drugs (Walsky et al, 2005 ). An approach using the combination of commercial antibody and chemical inhibitor against P450 3A has been reported (Rock et al, 2008 ), and showed a superior inhibition profi le of CYP3A4 compared with the use of antibody and chemical inhibitors individually.…”
Section: Inhibitory Cyp Antibodiesmentioning
confidence: 99%